Integrative phylogenetic, phylogeographic and morphological characterisation of the Unio crassus species complex reveals cryptic diversity with important conservation implications - M. Lopes-Lima; J. Geist; S. Egg; L. Beran; A. Bikashvili; B. Van Bocxlaer; A.E. Bogan; I.N. Bolotov; O.A. Chelpanovskaya; K. Douda; V. Fernandes; A. Gomes-dos-Santos; et al. (Molecular Phylogenetics and Evolution, 2024)

A nonsynonymous SNP within PCDH15 is associated with lipid traits in familial combined hyperlipidemia - Adriana Huertas-Vazquez; Christopher L. Plaisier; Ruishuang Geng; Blake E. Haas; Jenny Lee; Marleen M. Greevenbroek; Carla van der Kallen; Tjerk W. A. de Bruin; Marja-Riitta Taskinen; Kumar N. Alagramam; Päivi Pajukanta (Human Genetics, 2010)

Effects of testosterone and β‐glucan on immune functions in tench - A. Vainikka; E. I. Jokinen; R. Kortet; S. Paukku; J. Pirhonen; M. J. Rantala; J. Taskinen (Journal of Fish Biology, 2005)
A hormone manipulation was performed to examine the effects of testosterone on basal and β‐glucan‐induced immune functions in wild‐caught male and female tench Tinca tinca . Testosterone administration elevated testosterone concentration in plasma, but did not suppress lytic activity of plasma or the chemiluminescence response of blood or head kidney phagocytes in any of the three successive samples or in any of the treatment groups. Both testosterone and β‐glucan administrations had a negative effect on the relative mass of the spleen, and testosterone‐treated fish lost more mass than control fish. Males had a relatively larger spleen than females, but there were no gender differences in immune function. β‐glucan‐administration did not affect the plasma testosterone concentration.

Gender‐ and season‐dependent relationships between testosterone, oestradiol and immune functions in wild roach - A. Vainikka; E. I. Jokinen; R. Kortet; J. Taskinen (Journal of Fish Biology, 2004)
Plasma testosterone and 17β‐oestradiol concentrations, differential leukocyte counts and proportion of dead Rhipidocotyle campanula gill parasites (parasite resistance) were determined five times during a year in two populations of roach Rutilus rutilus and analysed for seasonal and gender differences. In addition to the above immune variables, plasma Immunoglobulin M (IgM) concentration, chemiluminescence and migration differential of head kidney phagocytes, size of the spleen, haematocrit and total leukocyte count were correlated with sex hormones for each population, sampling time and sex separately, using condition factor as a partial correlate. There were no clear gender differences in the determined immune variables. Both testosterone and oestradiol concentrations were lowest after the spawning in June. Oestradiol was higher in females than in males, but testosterone was present in equal concentrations in both sexes. Statistically significant correlations between sex hormones and immune variables were rare and mainly without any patterns with respect to population, sex or sampling date. The meta‐analysis on individual correlations, however, revealed a positive relationship of plasma testosterone concentration to chemiluminescence of head kidney phagocytes, plasma IgM concentration and the proportion of dead R. campanula to all R. campanula on the gills. In the meta‐analysis, the concentration of oestradiol was not found to correlate with any of the studied immune variables.

Poisoning caused by a mixture of plant-nutrient substrates - S. Takki; J. Heinonen; E. Taskinen (Archives of Toxicology, 1972)